Assessing the repair of critical size bone defects performed in a goat tibia model using tissue-engineered constructs cultured in a bidirectional flow perfusion bioreactor. (August 2014) - Gardel, LS; Afonso, M; Frias, C; Gomes, ME; Reis, RL
This work evaluated in vivo performance of a tissue-engineered bone-like matrix obtained by culturing cell-scaffold constructs in a flow perfusion bioreactor, designed to enable culture of large constructs, envisioning the regeneration of critical-sized defects. A blend of starch with polycaprolactone scaffolds was seeded with goat bone marrow stromal cells (GBMSCs) cultured in the perfusion bioreactor for 14 days using osteogenic medium. Cell seeded scaffolds cultured in static conditions acted as controls. After 14 days, constructs (42 mm length and 16 mm in diameter) were implanted in critical size defects performed in the tibial bone of six adult goats from which the bone marrow had been collected previously. Explants were retrieved after six and 12 weeks of implantation and characterized using scanning electron microscopy, energy-dispersive spectroscopy, micro-computed tomography and radiographic analysis to assess tissue morphology and calcification. Explants were histologically analyzed, using Hematoxylin & Eosin and Masson Trichrome staining. Results provided relevant information about the performance and functionality of starch with polycaprolactone–goat bone marrow stromal cell constructs in a critical size orthotopic defect performed in a large animal model and demonstrated that culture of the starch with polycaprolactone scaffolds with the autologous cells in perfusion culture provide a good therapy for the healing and regenerative process of bone defects.